Student Worksheets Based on Virtual Labs: Efforts to Optimize Science Practicum in Pandemic Time - Dyah Astriani; Tutut Nurita; Laily Rosdiana; An Nuril Maulida F; Siti Nurul Hidayati; Roihanna Waliyyul M (Universitas Muhammadiyah Sidoarjo, 2021)
The use of virtual lab-based students worksheet in science learning aims to optimize practicum activities during the pandemic. Virtual-based students worksheet take advantage of the features that are already available and adapted to the material to be practiced, so knowledge is needed to develop virtual lab-based students worksheet s. The activity of compiling virtual lab-based students worksheet was attended by science teacher participants from private schools in Gresik Regency, with the One Group Pretest Posttest design. Activity participants were given a pretest and then compiled a virtual lab-based students worksheet and posttest. The resulting students worksheet is assessed for feasibility using the students worksheet assessment instrument. The pretest and posttest data were analyzed by N-gain showing an increase of 0.64 in the medium category. The assessment of the participant students worksheet shows that the virtual lab-based students worksheet that have been created are in accordance with the instructions, the category is very feasible, so that it can be implemented as an effort to optimize science practicum during the pandemic.